Rfid Application For Designing Lowcost Learning Device For Play And Learning To Read Early Braille For Blind Children - Bertha Bintari W. (Universitas Sanata Dharma, 2023)
It is very important for children who have low vision or visual impairment to be able to recognize braille letters and recognize words. This ability will help them to be able to read and write Braille. Braille recognition learning methods currently use technology as a learning aid or assistive device. However, assistive devices with this technology are still rare and unaffordable for some schools and students in Indonesia. The design of this braille learning aid applies RFID as a low-cost solution for learning braille reading aids. This tool integrates several braille learning methods that have been carried out by teachers when teaching braille recognition in schools. The integrated methods are the Mangold method, the Fernald method, the Flashcards method and the scrabble method. This tool helps children recognize braille letters, arrange them as words and is confirmed directly by the tool through sound if the letters arranged as a word are right or wrong. With this integration method, children are expected to be able to learn to read braille while playing, and learn independently.